THE TRADITION OF FEEDING PEOPLE IN ASEMBAGUS SITUBONDO (STUDY OF LIVING HADITH) - Nurul Budi Murtini; Irfan Yuhadi (Al-Majaalis : Jurnal Dirasat Islamiyah, 2020)
Food amid humans is a great pleasure in the world because food is one of the sources of human life. Allah is the Rabb who gives food to humans to relieve their hunger. Among the characteristics of the occupants of Heaven is that they often feed the needy. Situbondo Regency is located on the north coast of Java, in the TapalKuda (Horseshoe) area. This research aims to investigate the motives and concept offeedingotherpeopleon Friday, the benefits of feeding people on Friday, and seek for ahadith that advocate feeding others. This research used a qualitative approach with the study of living hadith model. The results of this study indicate that: (1) The motives for feeding people are to get the benefits of sharing food with fellow Moslems, the desire to share, and be part of the social activity. Regular and non-permanent donors support the feeding concept. Food distribution is made every Saturday morning on the east side of AsembagusGreat (Jami') Mosque. Food is distributed to farmers, pedicab drivers, waste pickers, and people who could not afford it. (2) The benefits of feeding others are social care, more people, and laypeople interested in joining the study. (3) Several hadiththat prescribe to feed other people.